Implementasi Pembelajaran Tahfidzul Qur’an untuk Meningkatkan Karakter Qur’ani Siswa SMP Nurul Qudus Beji Pasuruan - Muhammad Fuad Zamroni; Ahmad Ma’ruf (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to describe the implementation of the Tahfidzul Qur’an learning program and its impact on shaping Qur’anic character among students at SMP Nurul Qudus Beji, Pasuruan. Tahfidz education is regarded as a strategic effort in developing religious, disciplined, responsible, and morally upright Muslim individuals. The research employs a qualitative approach using data collection techniques such as observation, interviews, and documentation. Data were analyzed using the Miles, Huberman, and Saldana model, which includes data condensation, data display, and conclusion drawing. The findings indicate that the Tahfidzul Qur’an program is integrated into the school curriculum, with class groupings based on students’ skill levels. Various memorization methods are used, including wahdah, talaqqi, takrir, and tasmi’, with a structured schedule to support learning consistency. The program contributes not only to improving students’ Qur’anic memorization but also significantly shapes their character—especially in aspects of discipline, responsibility, politeness, and spiritual awareness. Moreover, a collaborative learning environment encourages peer support and shared motivation. Despite existing challenges, such as low student motivation, time constraints, and internal or external distractions, dedicated teacher strategies and adaptive methods play a vital role in overcoming them. This research affirms that the Tahfidzul Qur’an program is an effective medium for cultivating a Qur’an-centered generation amidst modern challenges.